ANALISIS EFISIENSI PENGGUNAAN INPUT PRODUKSI USAHA TANI PADI DI KECAMATAN MENGWI KABUPATEN BADUNG - I Gusti Nyoman Ngurah Kerta Wijaya; Sudarsana Arka (Universitas Udayana, 2023)
Agriculture is the largest sector in any economy in developing countries. The agricultural sector is expected to be able to give a bigger role to farmers in determining the priority of agricultural business commodities which are the mainstay of business in Indonesia. The agricultural sector is one of the people's food providers, therefore the acceleration of agricultural development plays an important role in the provision of sufficient and affordable food for the community. This study aims to analyze the effect of harvested area, fertilizer and labor on farmers' production. This research was conducted in Mengwi District, Badung Regency. The object of research is harvested area, fertilizer, and labor. The population for this study were all rice farming in the Mengwi District, Badung Regency, totaling 3,571 people and the number of samples calculated using the slovin formula was 97 people. This study uses data collection techniques, namely observation, interviews, documentation and questionnaires. The analysis technique in this research is regression analysis. The results of this study are that harvested area has a positive effect on farmer production, fertilizer has a positive effect on farmer production, and labor has a positive effect on farmer production. keyword: Harvest Area,Fertilizer,Labor,Farmer's Production